Microorganisms in wild European reptiles: bridging gaps in neglected conditions to inform disease ecology research - Matteo Riccardo Di Nicola; Selene Rubiola; Anna Cerullo; Andrea Basciu; Claudia Massone; Thomas Zabbia; Jean Lou CM Dorne; Pier Luigi Acutis; Daniele Marini (International Journal for Parasitology: Parasites and Wildlife, 2025)
In Europe, reptiles remain among the vertebrates least addressed by conservation actions, despite being significantly impacted by human activities and environmental changes. Pathogenic microorganisms represent an additional yet poorly investigated threat to these animals, largely due to limited veterinary interest, which traditionally prioritises captive species over wild populations. Consequently, comprehensive studies on the pathogens affecting European wild reptiles remain sparse and fragmented, providing limited guidance for conservation strategies or health risk assessments.This review synthesises the current knowledge on potentially pathogenic microorganisms (namely bacteria, fungi, protozoa sensu lato and viruses) in wild, non-marine reptiles across Europe. We analysed 123 peer-reviewed studies from major scientific databases. Results indicate a marked increase in publications over the last two decades, although geographical and research focus biases persist. Southern European countries, notably Spain, Italy and Portugal, dominate the research landscape, while significant gaps exist in Northern and Eastern Europe. Lizards emerge as the most frequently studied hosts, especially in relation to apicomplexan parasites, followed by snakes and turtles. Among microorganisms, protozoa (particularly apicomplexans such as haemogregarines sensu lato) are the most frequently documented, whereas bacteria, fungi and viruses are less commonly reported, but significant from conservation and/or zoonotic perspectives. Within the latter, taxa such as Salmonella, Ophidiomyces and members of the Iridoviridae are relatively well represented. Molecular diagnostics have increasingly supplanted traditional microscopy, yet crucial tools such as culture-based methods and serology remain underutilised, limiting certain aspects of microorganism and disease characterisation.Bipartite host-microorganism network analysis revealed a specialised, modular structure promoted by specific microbial communities within particular hosts, themselves influenced by potential co-evolutionary dynamics or uneven sampling efforts.These findings underline the importance of integrating reptile disease ecology into wildlife conservation and public health frameworks, emphasising the urgent need to expand surveillance, particularly in underrepresented taxa and regions, to effectively address emerging disease threats under a One Health approach.